Terutroban versus aspirin in patients with cerebral ischaemic events (PERFORM): a randomised, double-blind, parallel-group trial. - Bousser, MG; Amarenco, P; Chamorro, A; Fisher, M; Ford, I; Fox, K; Hennerici, MG; Mattle, H; Rothwell, P; de Cordoüe, A; Fratacci, MD (2011)
BACKGROUND: Patients with ischaemic stroke or transient ischaemic attack (TIA) are at high risk of recurrent stroke or other cardiovascular events. We compared the selective thromboxane-prostaglandin receptor antagonist terutroban with aspirin in the prevention of cerebral and cardiovascular ischaemic events in patients with a recent non-cardioembolic cerebral ischaemic event. METHODS: This randomised, double-blind, parallel-group trial was undertaken in 802 centres in 46 countries. Patients who had an ischaemic stroke in the previous 3 months or a TIA in the previous 8 days were randomly allocated with a central interactive response system to 30 mg per day terutroban or 100 mg per day aspirin. Patients and investigators were masked to treatment allocation. The primary efficacy endpoint was a composite of fatal or non-fatal ischaemic stroke, fatal or non-fatal myocardial infarction, or other vascular death (excluding haemorrhagic death). We planned a sequential statistical analysis of non-inferiority (margin 1·05) followed by analysis of superiority. Analysis was by intention to treat. The study was stopped prematurely for futility on the basis of the recommendation of the Data Monitoring Committee. This study is registered, number ISRCTN66157730. FINDINGS: 9562 patients were assigned to terutroban (9556 analysed) and 9558 to aspirin (9544 analysed); mean follow-up was 28·3 months (SD 7·7). The primary endpoint occurred in 1091 (11%) patients receiving terutroban and 1062 (11%) receiving aspirin (hazard ratio [HR] 1·02, 95% CI 0·94-1·12). There was no evidence of a difference between terutroban and aspirin for the secondary or tertiary endpoints. We recorded some increase in minor bleedings with terutroban compared with aspirin (1147 [12%] vs 1045 [11%]; HR 1·11, 95% CI 1·02-1·21), but no significant differences in other safety endpoints. INTERPRETATION: The trial did not meet the predefined criteria for non-inferiority, but showed similar rates of the primary endpoint with terutroban and aspirin, without safety advantages for terutroban. In a worldwide perspective, aspirin remains the gold standard antiplatelet drug for secondary stroke prevention in view of its efficacy, tolerance, and cost. FUNDING: Servier, France.